Maternal near miss: a surrogate indicator of obstetrics care - Thakur, Anita; Jain, Madhu; Anuranjani, Lavanya; Srivastava, Yashi; Ambat, Gopika; Priya, Prerna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: A maternal near miss (MNM) is an event in which a pregnant woman is on the verge of dying but doesn’t die. Despite the fact that most maternal deaths can be avoided, efforts to reduce maternal mortality have not always been successful. This study aimed to identify and analyze the frequency of maternal near-misses (MNMs) cases and causes of maternal near miss due to severe obstetric complications. Methods: A retrospective observational study was carried out at Department of Obstetrics and Gynecology, Heritage Institute of Medical Sciences, Varanasi. The study duration was from January 2021-June 2022. Purposive sampling was used to collect the total of 2053 samples. Results: The study involved in total of 56 maternal near miss cases which includes total of ten maternal deaths. The majority of the respondents have more than 20 years of the age (82.1%) where near miss cases were higher in multiparous women (73.2%). First delays (delay in women seeking help) were almost a third in numbers to affect the maternal mortality and morbidity. Hypertension (32%). hemorrhage (20%) and anemia (14%) were the major leading cause of obstetrical complications. About 66% of the maternal near miss cases needed the interventional management that was ICU admission, mechanical ventilation (41.1%) and blood transfusion (32.1%). Conclusions: Pregnancy hypertension, postpartum hemorrhage, and severe anemia continue to be important determinants of maternal morbidity. First-referral unit facilities and training should be improved so that they can better respond to basic obstetric emergencies such as hypertension, anemia and hemorrhage.